Fermentation Kinetic and Alpha-Amylase Inhibition Studies of Mao Wine Fermented by Three Commercial Saccharomyces cerevisiae Yeasts - Sripakdee, Thitiya; Manochai, Kittika; Singkhan, Phummisak; Jandaruang, Jinda; Arthan, Supakorn; Siriwong, Khatcharin; Poomsuk, Nattawee (Trends in Sciences, 2024)
Mao wine is produced from mao (Antidesma thwaitesianum) and is a local beverage promoting Sakon Nakhon province, Thailand. Understanding the fermentation process is necessary in order to enhance the quality of mao wine products. This study aims to examine the kinetics of mao wine fermentation using 3 commercial types of Saccharomyces cerevisiae yeasts, namely Lalvin 71B, Lalvin RC212 and Lalvin K1-V1116, with an initial pH of 3.4, a sweetness of 22 % Brix and a yeast concentration of 0.4 g L–1 in controlled conditions at 25 °C for 10 days. The results revealed that the kinetic models, including logistic, Luedeking-Piret and modified Luedeking-Piret equations, are appropriate for analyzing the kinetics of yeast growth, alcohol production and reducing sugar, respectively. Lalvin K1-V1116 yeast yielded the highest capacity for alcohol production ( 113 g L–1), sugar-to-alcohol conversion (45 % conversion), and product efficiency (88 %), indicating its suitability for mao wine production. Furthermore, the investigation of the alpha-amylase inhibitory activity revealed that the IC50 values of mao wine samples were 2.88 - 4.78 mg mL–1, which were roughly 410 - 680 times greater than those of acarbose. These findings revealed the low efficacy of mao wine in inhibiting alpha-amylase activity. Nevertheless, a decrease in the level of inhibition may result in a decreased likelihood of side effects or undesirable reactions. This treatment is especially beneficial for people who have medication sensitivities. Additional research is required in order to substantiate its applicability in the management of type 2 diabetes. HIGHLIGHTS Mao wines were produced by 3 commercial cerevisiae yeast strains Lalvin K1-V1116 yeast exhibits the highest capacity in converting sugar to alcohol Lalvin K1-V1116 is the most suitable yeast for making mao wine The chosen kinetic models are appropriate for kinetic studies of fermentation process The efficacy of Mao wine in inhibiting the activity of alpha-amylase is quite low GRAPHICAL ABSTRACT